KAJIAN KOMUNIKASI PUBLIK: (SEBUAH ANALISIS PENERAPAN APLIKASI SUPERAPP POLRI UNTUK PELAYANAN SURAT KETERANGAN CATATAN KEPOLISIAN DI KEPOLISIAN RESOR SITUBONDO) - Hikmiyah, Maslachatul; Fanida, Eva Hany (Universitas Negeri Surabaya, 2024)
Public services are activities to fulfill community needs in the form of goods, services and administration by public service providers. The development of information technology is currently an important aspect inherent in social life. One of the benefits of the development of information technology is that it encourages public service providers to optimize efficient and responsive services. Realizing how important it is to provide good service, the National Police is making efforts to modernize it through Electronic Government, one of which is the SKCK application service which is presented in the form of a website. In 2023 the National Police will launch an innovation in the form of the Polri SuperApp application. However, in the implementation of online SKCK application processing, several obstacles were found, namely a lack of socialization and the application often had problems due to maintenance. Based on these obstacles, this research aims to analyze the application of the SuperApp Polri application for SKCK services at the Situbondo Resort Police. The type of research used is descriptive with a qualitative approach. The focus of this research uses the theory of e-government service quality according to Papadomichelaki and Metnzas with indicators of reliability, ease of use, trust, content and appearance of information, citizen support and functionality of the interaction. Data collection techniques through observation, interviews and documentation. The analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. The research results show that the implementation of the SuperApp Polri application in SKCK services at the Situbondo Police is quite good. User experience shows that using the Polri SuperApp application makes it easier for online SKCK applicants to get SKCK without having to ask for a letter of recommendation from the Sector Police. The recommendation that can be given is that the National Police needs to improve the quality of the Polri SuperApp application service in order to improve systems that often have problems and provide updated information regarding new policies on the Polri SuperApp Application.